Effects of Harvesting Frequency on Leaf and Root Yields of Cassava - Dahniya, M.T.; Oputa, C.O.; Hahn, S.K. (1981)
Total fresh leaf yield of cassava (Manihot esculenta Crantz) variety Isunikankiyan was not significantly affected by harvesting frequency, unlike variety TMS 30211. Compared with plants whose leaves were not harvested, there was a decrease in total fresh tuberous root yields of 56–76%, 34–62% and 15–32% when leaves were harvested at 1-, 2- and 3-month intervals respectively. The two cassava varieties reacted differently to leaf harvests in terms of tuber yields. Harvesting the top leaves of cassava at 2- or 3-month intervals is recommended to ensure reasonable yields of both leaves and tuberous roots.